Irish Witchcraft and Demonology - Seymour, St. John D. (St. John Drelincourt), 1880-1950 (Salt Lake City, UT : Project Gutenberg, 2013)
"Irish Witchcraft and Demonology" by St. John D. Seymour is a historical account written in the early 20th century. The work delves into the phenomenon of witchcraft in Ireland, positing that while witchcraft did not flourish to the same degree as in neighboring countries, it nonetheless had a presence, particularly through notable events like the case of Dame Alice Kyteler. Seymour aims to compile and analyze scattered historical records and tales of witchcraft and supernatural beliefs in Ireland. The opening of the text provides a thoughtful examination of the belief in witchcraft in Ireland, arguing against the common perception that the country was largely free from such phenomena. It discusses the historical context, noting that the Anglo-Norman and Protestant influences shaped the witchcraft narrative differently than in Celtic circles. With reference to various trials and societal responses, the author elucidates reasons for Ireland$1 (Bs relative immunity to widespread witch persecution, such as the lack of significant witchcraft literature and the political turmoil of the time. The introduction effectively sets the stage for deeper explorations into individual cases and broader cultural beliefs in subsequent chapters. (This is an automatically generated summary.)s
Release date is 2013-09-05
E-text prepared by the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Demonology; Witchcraft -- Ireland